Injuries in youth track and field are perceived to have multiple-level causes that call for ecological (holistic-developmental) interventions: a national sporting community perceptions and experiences - Jacobsson, J.; Bergin, D.; Timpka, T.; Nyce, J. M.; Dahlström, Ö. (Scandinavian Journal of Medicine & Science in Sports, 2018)
Engaging in competitive sports as a youth can have many health benefits, but recent studies also report a high risk for injury. The long-term purpose of this Swedish research program is to develop a framework for safe track and field training for young athletes (aged 12-15 years). The aim of this study was to establish what is perceived to contribute and cause injuries in youth track and field by compiling the best available experiential knowledge about the underlying factors and use this knowledge to identify appropriate areas to handle these in practical ways. Nine focus group interviews with in total 74 participants and confirming interviews with five individuals were performed in seven Swedish regions. Qualitative research methods were used for data analysis. Injuries in youth athletes were not considered to be strictly the result of individual factors but rather the result of the interactions between factors at different levels. Three major factors emerged: Insufficient knowledge for athletic development in daily practice; shortsighted communities of practice and sports policies not adjusted to youth; and societal health behaviors. The experiential knowledge in the national sporting community suggests that if effective and sustainable injury prevention processes are to be implemented for youth track and field, an ecological (holistic-developmental) approach to injury prevention is needed. Such an approach allows a longitudinal development-focused strategy for prevention that spans an athlete's entire career.